Assessing adherence to evidence-based guidelines of care for acne vulgaris. (2nd January 2022) - Dunaway, Spencer; Fleischer, Alan B.
Abstract: Background: Care guidelines are developed to assist in performing high-quality, cost-effective care. Objective: This study was designed to assess the adherence to evidence-based guidelines of care for acne. Methods: For acne treatment, we analyzed 2008–2015 National Ambulatory Medical Care Survey visits. For each medication mention, a grade was assigned based upon the American Academy of Dermatology 2007 treatment guidelines. Results: Most encounters achieved the grade of A, regardless of specialty or patient population. A proportion of visits involved the use of oral antibiotics monotherapy, which occurred at 11.7% (8.6–14.8) dermatologist and 25.6% (12.4–38.8) of non-dermatologist visits. Although not addressed in the 2007 guidelines, this practice was not recommended in the updated 2016 guidelines. Limitations: Other factors influencing prescribing behaviors cannot be completely assessed using extant data. Conclusion: This study demonstrates that nearly all physicians adhered to the 2007 guidelines. Many prescribed antibiotic monotherapy a practice not supported by the evidence. Capsule summary: Although acne practice guidelines are published, adherence to these guidelines is unknown. Using a grading system analogous to the United States A to F system, virtually all providers receive a grade of A. We expect that the grade will be lower in the future.